Structure-guided approach on the role of substitution on amide-linked bipyrazoles and its effect on their anti-inflammatory activity - Souraya A. Domiati; Khaled H. Abd El Galil; Mohammed A. S. Abourehab; Tamer M. Ibrahim; Hanan M. Ragab (Taylor & Francis Group, 2022)
A structure-guided modelling approach using COX-2 as a template was used to investigate the effect of replacing the chloro atom located at the chlorophenyl ring of amide-linked bipyrazole moieties, aiming at attaining better anti-inflammatory effect with a good safety profile. Bromo, fluoro, nitro, and methyl groups were revealed to be ideal candidates. Consequently, new bipyrazole derivatives were synthesised. The in vitro inhibitory COX-1/COX-2 activity of the synthesised compounds exhibited promising selectivity. The fluoro and methyl derivatives were the most active candidates. The in vivo formalin-induced paw edoema model confirmed the anti-inflammatory activity of the synthesised compounds. All the tested derivatives had a good ulcerogenic safety profile except for the methyl substituted compound. In silico molecular dynamics simulations of the fluoro and methyl poses complexed with COX-2 for 50 ns indicated stable binding to COX-2. Generally, our approach delivers a fruitful matrix for the development of further amide-linked bipyrazole anti-inflammatory candidates.